Palynological characterization of honey samples from Kwara State, Nigeria (Bangladesh Journal of Scientific and Industrial Research, 2017)
Palynological analysis of honey samples from different localities in Kwara State, Nigeria was carried out to isolate and identified pollen types in the honey samples. Out of forty two pollen types belonging to twenty two botanical families recovered, twenty five were identified to species level, eight to genus level and eight to family level. A total of 849,978 pollen grains were counted with 46,355 in Shao, 101,356 in Ganmo, 22,000 in Idofian, 28,337 in Omupo, 200,090 in Iludun Oro, 298,079 in Ijagbo, 22,100 in Offa I and 131,142 in Afon. The major pollen occurrences in the honey samples include those of Sarcocephaluslatifolius, Parkiabiglobosa, Phyllantusdiscoideus, Tridaxprocubens, Combretaceae/Melastomataceae, Spondiasmombins and Hymenocardiaacida. Other important honey plants identified are Elaeisguineensis, Lanneasp, Parinarisp, Celtissp and Entadaabssynica. All these are characteristic plant taxa of the Forest-Savanna ecotype of the studied area. The presence of relatively high quantity of pollen shows their richness in pollen composition and also a clear evidence that the honey are from botanical sourceand also multifloral.Bangladesh J. Sci. Ind. Res. 52(1), 7-14, 2017